2017
DOI: 10.1080/10942912.2017.1315593
|View full text |Cite
|
Sign up to set email alerts
|

Gelling properties of myosin as affected by L-lysine and L-arginine by changing the main molecular forces and microstructure

Abstract: This paper investigated the effects of L-lysine (Lys) and L-arginine (Arg) on the water-holding capacity (WHC) and hardness of myosin gel as well as the mechanism of these effects. The results showed that Lys, Arg, and KOH increased the WHC but decreased the hardness in all cases. At pH 6.32, the WHC increased in the order control < KOH < Lys ≈ Arg, while the hardness decreased in the order control > KOH > Lys > Arg. Lys shortened low field nuclear magnetic resonance spin-spin relaxation times (T 2 ), while Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…The addition of basic amino acids increased the WHC at all pHs except for pH 5.2, at which only 0.5% lysine resulted in a significantly higher WHC (P < 0.05). Histidine, lysine, and arginine have been reported to improve WHC of chicken salt soluble protein gel (Qin et al, 2015), chicken myosin gel (Fu et al, 2017), surimi gel (Cando et al, 2016), porcine myosin gel (Zhang et al, 2017), and pork sausage Zhou, Li, Tan, & Sun, 2014). Some of the studies attributed the enhanced WHC to basic amino acid-induced pH deviation away from pI (Fu et al, 2017;Qin et al, 2015;Zhou, Li, Tan, & Sun, 2014).…”
Section: Whc and Swelling Ratiomentioning
confidence: 99%
See 4 more Smart Citations
“…The addition of basic amino acids increased the WHC at all pHs except for pH 5.2, at which only 0.5% lysine resulted in a significantly higher WHC (P < 0.05). Histidine, lysine, and arginine have been reported to improve WHC of chicken salt soluble protein gel (Qin et al, 2015), chicken myosin gel (Fu et al, 2017), surimi gel (Cando et al, 2016), porcine myosin gel (Zhang et al, 2017), and pork sausage Zhou, Li, Tan, & Sun, 2014). Some of the studies attributed the enhanced WHC to basic amino acid-induced pH deviation away from pI (Fu et al, 2017;Qin et al, 2015;Zhou, Li, Tan, & Sun, 2014).…”
Section: Whc and Swelling Ratiomentioning
confidence: 99%
“…However, since the pH of the samples were controlled in the current investigation, factors other than pH shifting must have also contributed to the increased WHC. Basic amino acid-induced increase in protein solubility and hydration capacity (Li et al, 2019;Li et al, 2018), suppression of protein aggregation (Qin et al, 2015), reduction in water mobility (Fu et al, 2017;Zhang et al, 2017), and formation of a fine gel structure (Fu et al, 2017;Qin et al, 2015) have been suggested as possible mechanisms.…”
Section: Whc and Swelling Ratiomentioning
confidence: 99%
See 3 more Smart Citations